Factor Analysis of Student Discipline Implementing School Regulations at SD Negeri 101824 Durin Simbelang - Sri Destisa Ria Ginting (Asian Journal of Applied Education (AJAE), 2023)
This study aims to determine the factors causing the indiscipline of fifth grade students towards school regulations at SD Negeri 101824 Durin Simbelang. This research is a type of qualitative research. The research subjects consisted of 7 people including 5 students who had undisciplined characteristics, 1 homeroom teacher for class V, and 1 principal of SD Negeri 101824 Durin Simbelang. Collecting data using the method of observation, interviews, and documentation. Analysis of the research data used a qualitative descriptive method, namely the presentation of data in writing and describing it in accordance with the facts and data obtained from the research results. Checking the validity of the data in this study used a triangulation technique. The results of this study indicate that there are several factors that influence student indiscipline including family factors and school factors. Family factors, especially from the lack of attention from parents, families that do not get along well, low family economy and parents' education. School factors related to human rights include giving punishments that are still light in accordance with the current law which must give punishments to educate not through physical violence.